MUI HALAL CERTIFICATION ON MILKFISH SATAY AS AN EFFORT TO SUPPORT NATIONAL FOOD SECURITY - Palmawati Tahir; Muhamad Muslih; Rani Sri Agustina (Legal Standing : Jurnal Ilmu Hukum, 2020)
This study described the process of making milkfish satay which generally could be only for three days. Several trials were conducted for examining the level of expired milkfish satay and the result showed that milkfish satay could be for one week and one month even in cold temperatures (chiller/ freezers), it could be for three months. Because the resilience of this milkfish satay had been tested, this would certainly have positive impact on the producers. Besides, Indonesian Council of Ulama (Majelis Ulama Indonesia (MUI)) halal certification on some products was also considered very important because it would give confidence for people who would consume milkfish satay. The problem was there were some milkfish entrepreneurs who did not register their product, so they didn’t have halal certification. Besides, some milkfish satay entrepreneurs who had halal certification did not update it. The result of this study indicated that some milkfish satay entrepreneurs did not register their product. Therefore, they did not have halal certification from Indonesian Council of Ulama (Majelis Ulama Indonesia (MUI)). In addition, some milkfish satay entrepreneurs who had halal certification did not update it due to various reasons. Furthermore, this study was a qualitative and analytical descriptive study and it used primary and secondary data sources. Data sources were obtained from library and interviews with the milkfish satay entrepreneurs.